Optimal Control of McKean-Vlasov equations with controlled stochasticity - Di Persio, Luca; Kuchling, Peter (arXiv)
In this article, we analyse the existence of an optimal feedback controller of stochastic optimal control problems governed by SDEs which have the control in the diffusion part. To this end, we consider the underlying Fokker-Planck equation to transform the stochastic optimal control problem into a deterministic problem with open-loop controller.